Hubungan Anemia pada Kehamilan Dengan Inpartu Kala II Lama di BPM Ny. Suhariyati Surabaya - Ariesta, Ratna; Andriani, Dwi (Jurnal Ilmiah Kesehatan, 2016)
Relations of Anemia in Pregnancy With Inpartu Kala II Lama in BPM Ny. Suhariyati Surabaya. Anemia in pregnancy in Indonesia is still high, with a national rate of 65% which each region has different variations, anemia is one of the causes of prolonged labor. BPM Ny. Suhariyati Surabaya in December 2014 of 18 people inpartu obtained 6 (33.33%) who have anemia, of the 6 3 occurred prolonged second stage and 12 persons (66.7%) were not anemic, of the 12 people 3 people experiencing prolonged second stage. The purpose of this study was to determine the relationship between maternal anemia during long inpartu the second stage in the BPM Ny. Suhariyati Surabaya. This study uses an observational analytic study design and by the time the study was cross sectional study with a research population is all women berslin in BPM Ny. Suhariyati a total of 90 people for 2 months. Selection of the sample by simple random sampling with a large sample studied was 40. The variables in this study are anemic pregnant women and old stage II. At the time of data collection procedures inpartu using primary data and the processing of data by cross tables and chi square test. Based on the results of the study of 40 people found 14 (35.00%) had anemia which consists of 4 people (28.57%) had stage II normal and 10 (71.42%) experienced a prolonged second stage. The conclusions of this study is almost half inpartu mothers have anemia, mostly mothers inpartu experiencing prolonged second stage and there is a relationship between maternal anemia during inpartu with prolonged second stage. Advice for pregnant women should undergo hemoglobin levels every 3 months and taking 90 tablets Fe to pregnant women during pregnancy.